1998
DOI: 10.1577/1548-8659(1998)127<0128:eosagi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surgically and Gastrically Implanted Radio Transmitters on Growth and Feeding Behavior of Juvenile Chinook Salmon

Abstract: We examined the effects of surgically and gastrically implanted radio transmitters (representing 2.3–5.5% of body weight) on the growth and feeding behavior of 192 juvenile chinook salmon Oncorhynchus tshawytscha (114–159 mm in fork length). Throughout the 54‐d study, the 48 fish with transmitters in their stomachs (gastric fish) consistently grew more slowly than fish with surgically implanted transmitters (surgery fish), fish with surgery but no implanted transmitter (sham‐surgery fish), or fish exposed only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 16 publications
6
135
2
Order By: Relevance
“…Similarly, Adams et al (1998a) found that most juvenile Chinook salmon they studied (surgery incisions from sham surgeries or transmitter implantation) were well 64 healed by day 21, but incisions on 29% of the fish were slightly inflamed, reddened, or incompletely healed 21 d after surgery. They noted that by 54 d after surgery, only 21% of fish had similar incisions.…”
Section: Necropsymentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, Adams et al (1998a) found that most juvenile Chinook salmon they studied (surgery incisions from sham surgeries or transmitter implantation) were well 64 healed by day 21, but incisions on 29% of the fish were slightly inflamed, reddened, or incompletely healed 21 d after surgery. They noted that by 54 d after surgery, only 21% of fish had similar incisions.…”
Section: Necropsymentioning
confidence: 92%
“…Similarly, Adams et al (1998a) found that surgically implanted juvenile Chinook salmon had lower growth 21 d after implantation than control fish, but that there was no difference between the two groups 54 d after implantation.…”
Section: Growthmentioning
confidence: 94%
See 2 more Smart Citations
“…Transmitter treatment factors were 1) gastrically implanted radio transmitter, 2) surgically implanted radio transmitter, and 3) fish not implanted with a radio transmitter. Transmitters were implanted by U.S. Geological Survey (USGS) staff at McNary Dam using the methods of Adams et al (1998). Following implantation, Battelle staff freeze branded each fish with a unique external mark to provide a means to visually identify each individual fish during observation through acclimation, exposure, and post-exposure holding periods.…”
Section: Methodsmentioning
confidence: 99%